Development of agriculture value chains as a strategy for enhancing farmers’ income - P G Chengappa (Agricultural Economics Research Review, 2023)
At the outset, I express my sincere thanks to Dr. P K Joshi, the President, and esteemed members of the Agricultural Economics Research Association (AERA) for bestowing upon me the honour of President-Elect for 2017 annual conference of the Association. I am proud being associated with the Association since its inception, and had the privilege to serve it as its President and Vice President. On this occasion, I wish to place on record the yeomen services rendered by its past Presidents viz. Dr. A S Sirohi, Dr. C C Maji, Dr. Dayanatha Jha, Dr. V Rajagopalan, Dr. S S Johl, Dr. S S Acharya, Dr. Mruthunjaya and Dr. Karam Singh. I am happy that Dr. P K Joshi is now steering the Association to greater heights. I am also glad that the silver jubilee conference of the Association is hosted by the ICAR-National Academy for Research Management (NAARM), Hyderabad under the dynamic leadership of Dr. Ch. Srinivasa Rao. I sincerely appreciate the efforts of Dr. K Srinivas Rao, Organizing Secretary of the conference, faculty members and students for making excellent arrangements for this conference.